IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A-MATCH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKASISWA KELAS VII A SMP NEGERI 15 YOGYAKARTA - Imaeni Aqna (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purpose ofthis research was todescribe thetype of cooperativelearningmake-a-match in increasingmotivationandlearning achievementmath. This type of research isClassroom Action Research(CAR). The subjects inthis research werestudents of class VIIAof SMP Negeri15Yogyakarta, the numberof students36. The objects in this research are amathematicalmotivationandlearning achievementusingcooperative learning modelMake A-Match. Data collection techniques inthis research conductedby observation, inquirytechniques, documentation, andtest techniques. The results showed thatafter applying ofmathematics learningthroughcooperative learning modelmake-a-match, motivationandlearning achievementof mathematicshas increased. This is evidencedby an increase inthe averagepercentageof student motivationisseenfromthe results ofstudents' learningmotivation questionnaireonthe first cycle of67.03% increased to81.71% in the second cycle. In addition,students' mathematics learningachievementalso increasedfrom theinitial abilitystudentsan average valueof63.86into a72.38in the first cycleand the second cyclethe average valuebecomes78.64by80.56% KKMpercentage achieved. Thus the teacheradvised toapplycooperative learning modelmake-a-match as an alternativetoincreasestudentmotivationandlearning achievement.